Does photobiomodulation therapy combined to static magnetic field (PBMT-sMF) promote ergogenic effects even when the exercised muscle group is not irradiated? A randomized, triple-blind, placebo-controlled trial - Caroline dos Santos Monteiro Machado; Heliodora Leão Casalechi; Adriane Aver Vanin; Jônatas Bezerra de Azevedo; Paulo de Tarso Camillo de Carvalho; Ernesto Cesar Pinto Leal-Junior (BMC, 2020)
Abstract Background The direct application of photobiomodulation therapy (PBMT) using low-level laser therapy (LLLT) and light emitting diodes (LEDs) combined with a static magnetic field (sMF) (PBMT-sMF) to target tissues is shown to improve muscle performance and recovery. Studies have reported possible PBMT effects when a local distant to the target tissue is irradiated. Notably, the extent of these effects on musculoskeletal performance and the optimal site of irradiation remain unclear, although this information is clinically important since these aspects could directly affect the magnitude of the effect. Therefore, we investigated the effects of local and non-local PBMT-sMF irradiations on musculoskeletal performance and post-exercise recovery before an eccentric exercise protocol. Methods This randomized, triple-blind (participants, therapists and assessors), placebo-controlled trial included 30 healthy male volunteers randomly assigned to the placebo, local, and non-local groups. Active or placebo PBMT-sMF was applied to 6 sites of the quadriceps muscle of both legs. An eccentric exercise protocol was used to induce fatigue. The primary outcome was peak torque assessed by maximal voluntary contraction (MVC). The secondary outcomes were delayed onset muscle soreness (DOMS) measured by visual analogue scale (VAS), muscle injury assessed by serum creatine kinase activity (CK), and blood lactate levels. Evaluations were performed before the eccentric exercise protocol (baseline), as well as immediately after and 1, 24, 48, and 72 h upon protocol completion. Results Ten volunteers were randomized per group and analysed for all outcomes. Compared to the placebo and non-local groups, irradiation with PBMT-SMF led to statistically significant improvement (p < 0.05) with regard to all variables in the local group. The outcomes observed in the non-local group were similar to those in the placebo group with regard to all variables. The volunteers did not report any adverse effects. Conclusion Our results support the current evidence that local irradiation of all exercised muscles promotes ergogenic effects. PBMT-sMF improved performance and reduced muscle fatigue only when applied locally to muscles involved in physical activity. Trial registration NCT03695458 . Registered October 04th 2018.